2020
DOI: 10.1002/hyp.13880
|View full text |Cite
|
Sign up to set email alerts
|

Constraining water age dynamics in a south‐eastern Australian catchment using an age‐ranked storage and stable isotope approach

Abstract: Improving our knowledge of the travel times of water through catchments is critical for the management and protection of water resources and to improve our understanding of fundamental catchment behaviour. In this study we use the age-ranked storage framework StorAge Selection (SAS) to investigate travel times in the Corin catchment, a headwater catchment in the southeast of Australia covered by native Eucalyptus species. Few studies have applied the SAS framework globally and in energy-intensive areas where c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 86 publications
(189 reference statements)
2
10
0
Order By: Relevance
“…Our storage value is more consistent with the ∼ 1600 mm derived from depth to bedrock and porosity data used for the Colpach catchment (containing the Weierbach) that was modeled with CATFLOW (Loritz et al, 2017). Large differences between hydrometrically derived and tracer-derived storage estimates are not uncommon (Soulsby et al, 2009;Fenicia et al, 2010;Birkel et al, 2011) and, in fact, highlight the ability of tracers to reveal the existence of stored water that is not directly involved in streamflow generation (Dralle et al, 2018;Carrer et al, 2019). This hydraulically disconnected storage is nevertheless important for explaining the long residence times in catchments (Zuber, 1986).…”
Section: Limitations and Way Forward 441 Hydrometric-versus Tracer-inferred Storagesupporting
confidence: 76%
See 2 more Smart Citations
“…Our storage value is more consistent with the ∼ 1600 mm derived from depth to bedrock and porosity data used for the Colpach catchment (containing the Weierbach) that was modeled with CATFLOW (Loritz et al, 2017). Large differences between hydrometrically derived and tracer-derived storage estimates are not uncommon (Soulsby et al, 2009;Fenicia et al, 2010;Birkel et al, 2011) and, in fact, highlight the ability of tracers to reveal the existence of stored water that is not directly involved in streamflow generation (Dralle et al, 2018;Carrer et al, 2019). This hydraulically disconnected storage is nevertheless important for explaining the long residence times in catchments (Zuber, 1986).…”
Section: Limitations and Way Forward 441 Hydrometric-versus Tracer-inferred Storagesupporting
confidence: 76%
“…The storage value derived from unsteady travel times constrained by tracer data (Table 4; ∼ 1200-1700 mm) is noticeably larger than the maximum storage ( 250 mm) estimated from point measurements of porosity and water content (Martínez-Carreras et al, 2016), from water balance analyses (Pfister et al, 2017), from water balance analyses combined with recession techniques (Carrer et al, 2019), and from a distributed hydrological model (≤ 700 mm, Glaser et al, 2016Glaser et al, , 2020. Our storage value is more consistent with the ∼ 1600 mm derived from depth to bedrock and porosity data used for the Colpach catchment (containing the Weierbach) that was modeled with CATFLOW (Loritz et al, 2017).…”
Section: Limitations and Way Forward 441 Hydrometric-versus Tracer-inferred Storagementioning
confidence: 75%
See 1 more Smart Citation
“…Furthermore, we modified the parameterization of SAS functions in the mHM‐SAS model. In this study, we focus on the two‐parameter beta function (Equation ) because of its flexibility in representing different types of selection preferences for outflows and its practical use (Buzacott et al., 2020; J. Yang, Heidbüchel, et al., 2018; Nguyen et al., 2021; van der Velde et al., 2015). In previous studies, the temporal variability of the beta function parameters was restricted to certain limited types of selection preferences.…”
Section: Methodsmentioning
confidence: 99%
“…controls are transferable. Buzacott et al (2020) also found that high evapotranspiration and deep groundwater sources (this time in fractured bedrock aquifers) had a strong influence on the Corin catchment in the Australian Alps. They used time series of stable isotope data in precipitation and stream flow to identify storage selection (SAS) functions to estimate the ages of stream flow, catchment storage, and evapotranspiration.…”
Section: Water Ages In Seasonally Wet Catchments In Australiamentioning
confidence: 96%